MiRNA-Seq reveals key MicroRNAs involved in fat metabolism of sheep liver - Fei, Xiaojuan; Jin, Meilin; Yuan, Zehu; Li, Taotao; Lu, Zengkui; Wang, Huihua; Lu, Jian; Quan, Kai; Yang, Junxiang; He, Maochang; Wang, Tingpu; Wang, Yuqin; et al. (Frontiers in Genetics, 2023)
MicroRNAs (miRNAs) are a kind of small RNA that have important functions in proliferation, differentiation, metabolism, and disease. The function of miRNAs in sheep liver fat metabolism has not been thoroughly elucidated. There is a genetic difference between Hu sheep (short/fat-tailed sheep) and Tibetan sheep (short/thin-tailed sheep) in tail type. Previous studies have mainly focused directly on sheep tail fat, which is not the main organ of fat metabolism. In this study, miRNA-Seq was used to identify miRNAs in the liver tissue of three Hu sheep (short/fat-tailed sheep) and three Tibetan sheep (short/thin-tailed sheep) to characterize the differences in fat metabolism of sheep. Hu sheep was in a control group, and 11 differentially expressed miRNAs (DE miRNAs) were identified, including six up-regulated miRNAs and five down-regulated miRNAs. Miranda and RNAhybrid were used to predict the target genes of DE miRNAs, obtaining 3404 target genes. A total of 115 and 67 GO terms as well as 54 and 5 KEGG pathways were significantly (padj < 0.05) enriched for predicted 3109 target genes of up-regulated and 295 target genes of down-regulated miRNAs, respectively. Furthermore, functional validation using the dual-luciferase reporter assay indicated that the up-regulated miRNA; oar-miR-432 potentially targeted sirtuin 1 (SIRT1) expression. The expression of oar-miR-432 in the liver tissue of Hu sheep was higher than that in Tibetan sheep. The expression of SIRT1 in the liver tissue of Tibetan sheep was higher than that in Hu sheep. At the transcriptional level, SIRT1 was negatively regulated by oar-miR-432. The result of Western blot showed that the expression of SIRT1 was negatively regulated by oar-miR-432 in preadipocytes. These results could provide a meaningful theoretical basis for studying the fat metabolism of sheep.